Pengaruh Coorporate Governance, Leverage, Ukuran Perusahaan, dan ROA Terhadap Tax Avoidance (Studi Kasus Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia) - Erna Chotidjah Suhatmi; Dessy Ambarsari (Jurnal Akuntansi dan Pajak, 2023)
Tax is a very important component for the state, especially in national development. This indirectly indicates that both individuals and entities must also comply with their obligations to pay taxes consciously and voluntarily. It is noted that until now there are still many companies that avoid paying taxes, especially companies in the manufacturing sector. This study aims to determine the effect of corporate governance, leverage, firm size, and ROA on tax avoidance. The research approach used in this research is quantitative. This method is a data presentation that is dominated by numbers and statistical data analysis to test the hypotheses that have been announced beforehand. The data was obtained from the IDX's official website, namely www.idx.co.id. After screening the data, the researchers obtained 14 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in accordance with predetermined criteria. The data analysis method used in this research is multiple regression. Based on the results of research that has been carried out, it is found that the simultaneous test shown by the F test is known to have a sig-F value (p < 0.05) indicating that the variables of corporate governance, leverage, firm size, and ROA together have a significant effect on tax avoidance. . The partial test that has been carried out with the t test shows that there are two variables that affect the tax avoidance variable, namely institutional ownership and ROA.